Professional Perspectives on the Task of Guidance in Professional Technical Colleges (PTC): Challenges and Opportunities - Murillo Aguilar, Osvaldo (2024)
The study presented in this article was developed within the framework of Project 724-C1-714 Thematic Observatory of Costa Rican Technical and Vocational Education and Training, registered at the Institute for Research in Education of the University of Costa Rica. In this qualitative study, with a descriptive scope, the phenomenological method and the questionnaire were used as a technique for the collection of information; 8 of 11 Guidance professionals who work in the Professional Technical High Schools of the Regional Educational Directorate of Puriscal of the Ministry of Public Education participated. It was carried out during the second cycle of 2022 and the first cycle of 2023. The information obtained was grouped into 3 categories: Status of the Technical and Vocational Education and Training, About Guidance in the Professional Technical High Schools and Guidance in the Professional Technical High Schools over the next five years. As part of the results, it is highlighted that the people consulted foresee a positive future for Technical and Vocational Education and Training, due to the attention that is being given in Costa Rica to this educational modality, based on the need for young people to join the world of work, which leads to the mention of the opportunities that Guidance has in this context. In this regard, it is indicated in relation to Vocational Guidance, the exploration of interests, skills and knowledge of the environment. This depends on the vocational decision-making associated with the specialty they are going to study, their incorporation into the world of work and the possibility of continuing or not with tertiary education. Regarding the challenges, the need to have spaces that allow students to be offered vocational guidance is indicated, specifically the lesson of Guidance for the diversified cycle is mentioned. Among the conclusions obtained are that; Technical and Vocational Education and Training is an educational modality that allows the country to increase its competitiveness and opens opportunities for the student population to obtain a job. However, it is stated that there are aspects that must be paid attention to in order to improve this educational modality. It is mentioned, for example, that administrative management should seek to create spaces to offer vocational guidance. The opportunities that arise for Guidance in the Professional Technical High Schools refer to actions to be developed from Vocational Guidance, exploration of the interests and abilities of the students and for knowledge of the environment. As challenges, the need to be able to involve students in their processes of self-knowledge, decision-making and life project is emphasized. It is considered that in the immediate future, Guidance must integrate the use of Information and Communication Technologies into its work, which requires that continuous training processes be planned for the group of professionals in Guidance.